Exploring psychological resilience of entrepreneurial college students for post-pandemic pedagogy: The mediating role of self-efficacy - Guo, Hui; Zhang, Yu; Tian, Yaqi; Zheng, Wenxiu; Ying, Limeng (Frontiers in Psychology, 2022)
The psychological impact of the COVID-19 epidemic on college students is an important topic. With the entry of the post-epidemic era, how universities can better improve students’ psychological resilience in teaching is the research topic of this article. In the form of a questionnaire survey, some entrepreneurial college students investigated the loneliness and psychological resilience of college students after the outbreak of the epidemic and explored the role of self-efficacy in it. The data is collected online through cooperation with an entrepreneurial event, and the participating students are asked for background information such as colleges, grade, and majors. After collecting this information, they answered a series of simplified scale questions about loneliness, self-efficacy, and psychological resilience. In the end, a total of 200 questionnaires from different universities were collected, and the structural equation model was used to explore the role of self-efficacy. The results show that: loneliness has a significant negative effect on Self-efficacy, β = -0.292, p < 0.001; Self-efficacy has a significant positive effect on psychological resilience, β = 0.556, p < 0.0 01; loneliness has a significant negative effect on psychological resilience, β = -0.244, p < 0.01. Self-Efficacy has a significant intermediate effect in loneliness and psychological resilience, with an effective value of -0.111 and p < 0.01. The results show that this exploratory survey finds it important to provide targeted personal self-efficacy improvement activities for college students with a strong sense of loneliness and to combine school and family education organically to help college students form a healthy and upward mentality to better cope with the unknown and troubles caused by the epidemic, which will help improve the psychological resilience of college students in the epidemic.